Mapping the Landscape of Culturally Responsive Teaching: A Review on Bicultural Materials, Instructional Strategies, and Learning Outcome - Muhammad Agung; Andi Nur Annisa; Nella Yuadiah Ningsih; Musdalifah (Universitas Islam Negeri Palopo, 2025)
This systematic literature review maps the landscape of Culturally Responsive Teaching (CRT) in English as a Foreign Language (EFL) contexts, with a focus on Indonesia’s setting. Guided by the PRISMA framework, the review synthesizes 20 recent studies (2024-2025) to analyze the integration of bicultural materials or culturally nuanced resources, the instructional strategies employed, and the resulting learning outcomes. Findings reveal that effective CRT implementation predominantly utilizes multimodal, project-based strategies, such as comparative cultural analysis, digital storytelling, and role-play, leveraging culturally nuanced resources like local folklore, artifacts, and traditions. The synthesis demonstrates that this pedagogical approach yields a dual benefit: it significantly enhances specific English language competencies (notably vocabulary mastery, writing, and speaking skills) while concurrently fostering critical socio-affective outcomes, including strengthened cultural identity, intercultural awareness, student motivation, and critical thinking. The study presents evidence-based strategies grounded in practical application to effectively pair local content with interactive pedagogy. These findings contribute to the discourse on equitable language learning by providing a validated map of practices that support both language achievement and cultural competence. The study advances the field by proposing integrated frameworks for material selection and instructional strategy to enhance holistic learning, while underscoring the necessity for further empirical research across diverse K-12 settings to validate and adapt these approaches.